Retrospective study of bovine besnoitiosis in the Auvergne Rhône-Alpes region in France - Lahondes, Tiphaine; Carolino, Nuno; Sousa, Sérgio Ramalho; Waap, Helga; Martins, Elisabete Gomes (Frontiers in Veterinary Science, 2025)
Bovine besnoitiosis is a parasitic disease caused by the parasite Besnoitia besnoiti. It was classified as an emerging disease by EFSA in 2010, due to the appearance of new cases in several European countries. The clinical presentation can be acute or chronic, but most animals remain asymptomatic, acting as reservoirs. The disease is associated with important economic losses and strict control measures are necessary to mitigate the spread of infection. In recent years, the Health Defense Group of the Auvergne Rhône-Alpes region in France has implemented a voluntary program to monitor the presence of the infection in dairy cattle, through the testing of bulk milk samples collected in dairy farms. The aim of this study was to assess the distribution and evolution of the disease from January 1, 2020 to July 1, 2023. The official results of bulk milk tests from 7,552 dairy farms in all 12 departments of the region were analyzed. The milk samples were tested in certified laboratories using an indirect ELISA (ID Screen® Besnoitia Milk Indirect, IDVET laboratory). Descriptive statistics, sample proportions and disease prevalence were calculated for each year and department. The effects of department, year of analysis, farm type, and number of analyses on the risk of a farm testing positive was investigated. In all the departments, more than 96.2% of active farms were tested in at least 1 year of the study period, with most departments conducting testing annually. Of the farms tested, 12% were positive in at least 1 year. Prevalence varied significantly over the study period and between departments (p < 0.01). The lowest prevalence was observed in the Rhône department in 2021, at 0.36%, while the highest prevalence of 23.44% was recorded in the Savoie department in the same year, based on a testing coverage of 97.5% and 100% of active farms, respectively. The probability of a farm testing positive was 4.1% when only one sample was collected annually, increasing to 7.3%, 12.6% and 20.9%, when two, three and four samples were collected respectively. Farms with mixed production types had a higher probability of testing positive. The present study reinforces the importance of regular, repeated testing and focused monitoring of farms with higher risk profiles, such as mixed-production operations, to effectively control and manage bovine besnoitiosis.